Thrombosis of the Left Pampiniform Plexus After Scleroembolization Procedure for Varicocele (British Journal of Multidisciplinary and Advanced Studies, 2025)
Thrombosis of the pampiniform venous plexus is a very rare pathology, mainly affecting the left spermatic vein and is one of the causes of acute scrotal pain. It presents with initial symptoms, such as pain and testicular swelling, which may be nonspecific for thrombotic disease and they may simulate other acute local conditions. Color Doppler Ultrasound is the main examination for diagnosis. For the few cases available in the literature, the etiology and pathophysiology of spermatic vein thrombosis remain unclear and, for the same reason, the differential diagnosis and the therapeutic approach, conservative vs surgical, still raise numerous controversies. In this work, the Authors report a very particular case of left pampiniform plexus venous thrombosis that occurred in a young patient a few hours after the scleroembolization procedure for the minimally invasive treatment of varicocele.